Pengaruh Abu Vulkanis Gunung Agung dan Pupuk Kompos terhadap Beberapa Sifat Tanah dan Hasil Kacang Tunggak (Vigna unguiculata (L.) Walp.) - I WAYAN NARKA; I NYOMAN DIBIA; I WAYAN DANA ATMAJA (Agrotrop : Journal on Agriculture Science, 2021)
The Effect of the Mount Agung Volcanic Ash and Compost on Soil Properties and Yield of Tunggak Nuts (Vigna unguiculata (L.) Walp). The purpose of this study was to determine the effect of giving volcanic ash and compost as a soil amendment. The design used was a factorial randomized block design. The volcanic ash factor consisted of 3 levels: A0 = no volcanic ash, A1 = 15% volcanic ash and A2 = 30% volcanic ash. The compost factor consisted of 3 levels: K0 = without compost, K1 = 10 tons of compost ha-1, and K2 = 20 tons of compost ha-1. The combination treatments was repeated 3 times so that there were 27 observation units. Several parameters of soil properties and yield of tunggak nuts were studied to determine the effect of volcanic ash and compost as soil amendments. The results showed that the interaction between the treatment of volcanic ash and compost on the soil and plants was not significant, while the single treatment of compost had a significant effect on the growth and yield of tunggak nuts. The treatment of volcanic ash has not shown a significant effect, both on soil and on plant growth and yield.